Submental island flap reconstruction for carcinoma of the oral cavity: Experience in 30 cases - Pradeep Pradhan (KeAi Communications Co., Ltd., 2019)
Objective: The submental flap can be utilized for soft tissue reconstruction in oral cavity malignancies because due to its close approximation to the surgical site, fewer donor site morbidity and the cost effectiveness of the procedure. Methods: A total of 30 patients with squamous cell carcinoma of the oral cavity were included in the study from July 2012 to August 2015 in a tertiary care referral hospital. Patients with clinical staging I/II/III (T1/T2/T3, N0) oral malignancy were included in the study. Patients with nodal metastasis irrespective of the stage of disease and patients with chronic medical illness/revision cases were excluded from the study. Submental island flap was utilized for the reconstruction of the soft tissue defect in each patient. Patients were followed at monthly interval till 6 months in the postoperative period. Results: The buccal mucosa (12 patients), tongue (10 patients) and floor of mouth (8 patients) were the subsites in the oral cavity. Partial and complete skin necrosis was found in 4 and 2 patients respectively. Postoperative chemoradiation was required in 5 patients. None of the patients had loco regional recurrence till 6 months of follow-up. Conclusion: The submental island flap is considered to be the reliable option for the soft tissue reconstruction in oral cancer because of dependent vascular pedicle, less donor site morbidity and the lower cost compared to the free flaps, often preferred in patients with a lower socioeconomic condition. Keywords: Oral malignancies, Submental island flap, Surgical technique, Outcome